2011
DOI: 10.4097/kjae.2011.60.3.161
|View full text |Cite
|
Sign up to set email alerts
|

The BIS and hemodynamic changes in major burn patients according to a slow infusion of propofol for induction

Abstract: BackgroundMany pathophysiologic alterations in patients with major burns can cause changes in the response of propofol. The aim of this study is to determine the appropriate induction dose of propofol using a slow infusion rate for major burn patients to obtain desirable sedation and hypnotic conditions with minimal hemodynamic changes.Methods45 adults with major burns and who were electively scheduled for escharectomy less than a week after injury were recruited. For induction with propofol, the patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Among studies on BIS, very few of them compare intraoperative haemodynamic variables. Some of them are experimental, some of them are performed on a small number of patients and some only evaluate the intubation period (13)(14)(15). We observed that the heart rates of the control patients in the 1 st and 2 nd period were statistically significantly higher than that of the BIS patients.…”
Section: Discussionmentioning
confidence: 85%
“…Among studies on BIS, very few of them compare intraoperative haemodynamic variables. Some of them are experimental, some of them are performed on a small number of patients and some only evaluate the intubation period (13)(14)(15). We observed that the heart rates of the control patients in the 1 st and 2 nd period were statistically significantly higher than that of the BIS patients.…”
Section: Discussionmentioning
confidence: 85%
“…Others have shown temporal correlations between BIS and conventional sedation measures, 24,25 suggesting that BIS monitoring is useful for evaluating sedation. 4,24 Both the depth of sedation and BIS values have been shown to correlate with the level of spinal block. 6,15 Secondly, BIS is sensitive to internal or external patient circumstances and can be affected by abrupt arousal, movement, coughing or noise in patients with light or no additional sedation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, BIS-guided anesthesia lead to reductions in use of hypnotics. [ 1 4 11 ] Recently, its use has been extended to ICU patients. [ 14 15 24 26 ] The present study analyzes the utility of BIS monitors in mechanically ventilated patients in trauma ICU.…”
Section: Introductionmentioning
confidence: 99%